2019
DOI: 10.3389/fmicb.2019.01428
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Transduction Protein PII Controls Ammonium, Nitrate and Urea Uptake in Cyanobacteria

Abstract: P II signal transduction proteins are widely spread among all domains of life where they regulate a multitude of carbon and nitrogen metabolism related processes. Non-diazotrophic cyanobacteria can utilize a high variety of organic and inorganic nitrogen sources. In recent years, several physiological studies indicated an involvement of the cyanobacterial P II protein in regulation of ammonium, nitrate/nitrite, and cyanate uptake. However, direct interaction of P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 95 publications
0
73
0
Order By: Relevance
“…A feature distinguishing the E. coli and Synechococcus proteins is their mode of covalent modification under N-limiting conditions: whereas PII from E. coli and other proteobacteria is uridylylated by a Gln-regulated uridylyl-transferase at a tyrosine residue (Y51) located on the large surfaceexposed T-loop, the cyanobacterial PII protein is phosphorylated at a neighbouring seryl residue (S49) by an as yet uncharacterized protein serine kinase activity (Sp€ at et al, 2015). Modification of the T-loop, together with the binding of effector molecules, determines the interaction of PII with various targets (enzymes, transport channels, transcription factors and other target proteins) (Huergo et al, 2013;Watzer et al, 2019).…”
Section: Evolution Of Pii Proteins: From Cyanobacteria To Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A feature distinguishing the E. coli and Synechococcus proteins is their mode of covalent modification under N-limiting conditions: whereas PII from E. coli and other proteobacteria is uridylylated by a Gln-regulated uridylyl-transferase at a tyrosine residue (Y51) located on the large surfaceexposed T-loop, the cyanobacterial PII protein is phosphorylated at a neighbouring seryl residue (S49) by an as yet uncharacterized protein serine kinase activity (Sp€ at et al, 2015). Modification of the T-loop, together with the binding of effector molecules, determines the interaction of PII with various targets (enzymes, transport channels, transcription factors and other target proteins) (Huergo et al, 2013;Watzer et al, 2019).…”
Section: Evolution Of Pii Proteins: From Cyanobacteria To Plantsmentioning
confidence: 99%
“…Early work showed that the expression of AtGLB1, the gene encoding PII in Arabidopsis, is controlled by light but also by N and C metabolites, as the AtGLB1 mRNA levels are repressed by amino acids and induced by sucrose (Hsieh et al, 1998). Nitrite uptake and sensitivity were shown to be higher in Arabidopsis PII knockout mutants than in the wild-type (Ferrario-M ery et al, 2005;Ferrario-M ery et al, 2008), implying that the PII-mediated regulation of nitrite uptake by Arabidopsis chloroplasts is similar to that by cyanobacteria (Watzer et al, 2019). Further research identified WRINKLED1 as a transcription factor inducing AtGLB1 in Arabidopsis seeds at the onset of the maturation phase (Baud et al, 2010).…”
Section: Functions Of Pii Derived From Gene Expression and Mutant Anamentioning
confidence: 99%
“…In addition to the regulation of enzyme activities via PII, the trimeric protein can also influence transport activities. Recent pull-down analysis revealed that PII regulates an ensemble of nitrogen transport complexes, involving the NRT nitrate/nitrite transport system, the URT urea transport system and the ammonium transporter AMT1 through direct protein-protein interaction (12).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous PII-pull down study, several putative PII interactors of unknown function had been identified (12). The most prominent among these was the product of the sll0944 gene, a member of the NtcA regulon (13).…”
Section: Introductionmentioning
confidence: 99%
“…Like in plants, serine biosynthesis in cyanobacteria involved light-dependent photo-respiratory and light-independent phosphoserine pathways (Klemke et al, 2015). The concentration of urea was also increased 1.67-folds than that of the wild type, in accordance with the up-regulation of several amino acids such as glycine in cyanobacteria (Esteves-Ferreira et al, 2018;Watzer et al, 2019). Three monosaccharides, including D-glucose involved in glycolysis process, methyl-Dgalactopyranoside and D-altrose were also up-regulated by more than 2.65-folds respective to the wild type, in line with the possible function of Sll1330 in glycolysis, which was revealed by a previous study that the knockout of sll1330 could cause the accretion of these monosaccharide (Tabei et al, 2007).…”
Section: Metabolic Changes In Seven Most Regulated Rr Mutantsmentioning
confidence: 84%